Drug-induced hypersensitivity syndrome related to piperacillin-tazobactam: a case report and review of the literature - Shen, Ya; Cui, Shun-shun; Teng, Xiao-bao; Han, Ming-feng (Frontiers in Medicine, 2024)
Allergic reactions to drugs caused by piperacillin-tazobactam are common in clinical practice. However, we also found a few cases of drug-induced hypersensitivity syndrome (DiHS)/Drug reaction with eosinophilia and systemic symptoms (DRESS) caused by piperacillin-tazobactam in our clinical work. We report a case of a 60-year-old female patient who was treated with piperacillin-tazobactam anti-infective therapy after the diagnosis of hematogenous lung abscess, developed fever, rash, and blood abnormalities after 26 days of application, and was later diagnosed as DIHS, which was improved after the administration of glucocorticoid and anti-allergic drugs. In addition, we also retrospectively analyzed 17 cases of DiHS caused by piperacillin-tazobactam from the PubMed databases between March 1980 and September 2023. The majority of the patients had an incubation period of more than 14 days, and the common clinical features included elevated eosinophil count/percentage, fever, rash, liver damage, and lymph node enlargement. After treatment with topical or systemic glucocorticoids, 16 of the 17 patients improved and one died because of the underlying condition. The clinical features of DiHS were diverse and included a long incubation period, skin rash, elevated eosinophils, and impaired organ function. Since some patients have atypical clinical features, clinicians should raise awareness of the disease, recognize these features early, and treat them promptly.